Pengaruh Proporsi Tepung Sagu (Metroxylon sagu Rottb.) dan Tepung Sorgum (Sorghum bicolor L. Moench) terhadap Pati Resistan, Kandungan Gizi, dan Sifat Organoleptik Kukis untuk Diabetes Melitus Tipe 2: The Effect of Sago (Metroxylon sagu Rottb.) Flour and Sorghum (Sorghum bicolor L. Moench) Flour Proportion on Resistant Starch, Nutrient, and Organoleptic Properties of Cookies for Type 2 Diabetes Mellitus - Lestari, Hana Tri; Fauziyah, A'immatul; Nasrulloh, Nanang (Universitas Airlangga, 2025)
Background: Basic Health Research (2018) reported that the prevalence of diabetes mellitus (DM) among individuals aged 15 years and older is 8.5%, with 90–95% of them being type 2 diabetes mellitus (DMT2). Therefore, corrective action through food modification is needed to control blood glucose. Sago and sorghum contain resistant starches that can enhance glycemic and insulin response. Objectives: To analyse the effect of the proportion of sago flour and sorghum flour on resistant starch, nutritional content, and organoleptic properties of cookies designated for T2DM. Methods: This study employed a Complete Randomised Design with 5 variations of sago flour and sorghum flour treatment, namely F1 (100%:0%), F2 (75%:25%), F3 (50%:50%), F4 (25%:75%), and F5 (0%:100%), each replicated twice. The analysis of resistant starch and nutritional content utilised a one-way ANOVA test, followed by the Duncan test for significant differences. Organoleptic properties were assessed using the Kruskal Wallis test. The best formulations were determined based on the De Garmo method. Results: The results revealed significant differences in resistant starch (p-value=0.002), protein (p-value<0.001), carbohydrate (p-value=0.012), and ash content (p-value=0.005). No significant differences were observed in fat (p-value=0.514), moisture content (p-value=0.881), colour (p-value=0.891), aroma (p-value=0.061), texture (p-value=0.164), and taste (p-value=0.421). The F2 formulation emerged as the best, containing 6.31% resistant starch, 7.34% protein, 23.69% fat, 50.95% carbohydrates, 16.19% moisture content, and 1.84% ash content. Conclusions: The proportion of sago flour and sorghum flour significantly affected the content of resistant starch, protein, carbohydrates, and ash content, but not fat, moisture content, and organoleptic properties.